2014
DOI: 10.1002/ecj.11595
|View full text |Cite
|
Sign up to set email alerts
|

Development of Estimation Method of Spatial Average Irradiance Fluctuation Characteristics Considering Smoothing Effect around Observation Point

Abstract: In order to estimate the total power output fluctuation of a high-penetration photovoltaic power generation system by using data from a limited number of points, the smoothing effect around individual observation points should be taken into account. Based on the transfer hypothesis, this study proposes a low-pass filter (LPF) to estimate the spatial average irradiance fluctuation characteristics taking the smoothing effect around the observation point into account. First, by using the irradiance data observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It has been confirmed that the variation rate becomes smaller when the wind power generation outputs are added, which is called the smoothing effect. Theoretically, it is considered that the standard deviation of the total output becomes N 0.5 times the standard deviation of the individual output while adding N outputs that are not correlated with one another [6] [7]. For example, consider summing the independent N outputs with a rated capacity of 1 kW.…”
Section: Central Limit Theoremmentioning
confidence: 99%
“…It has been confirmed that the variation rate becomes smaller when the wind power generation outputs are added, which is called the smoothing effect. Theoretically, it is considered that the standard deviation of the total output becomes N 0.5 times the standard deviation of the individual output while adding N outputs that are not correlated with one another [6] [7]. For example, consider summing the independent N outputs with a rated capacity of 1 kW.…”
Section: Central Limit Theoremmentioning
confidence: 99%
“…Actual monitored solar irradiation data (minute by minute) for Osaka, Japan, were used to generate the fluctuation in the output power of the PV system. We considered the spatial smoothing effect of the solar irradiation data based on the transfer hypothesis [31,32]. Moreover, based on this hypothesis, we have analyzed the effect of spatial smoothing on the variation in line temperature; this paper adopted Case B (where the area is 100 km 2 ) in [33].…”
Section: Simulation Conditionsmentioning
confidence: 99%
“…Similarly, [10] has used the power spectral density approach to investigate the VRI of six PV systems that are spread over 1100 km 2 geographical area in Spain using one‐second data resolution. In [11], a signal decomposition hypothesis has been used to analyse the variability of 18 sensors of the global horizontal irradiance (GHI) distributed within a radius of 30 km in Nagoya, Japan, using a Fast Fourier transform‐based analysis with data sampled in one‐minute resolution. Another method has been used in [12] in which the standard deviation is employed to evaluate the geographic smoothing for a group of 16 PV systems dispersed within 1500 km in Ontario, Canada, using a one‐hour irradiance resolution.…”
Section: Introductionmentioning
confidence: 99%